Design and implementation of low power encoder incorporating adaptive modulation for multi user OFDM system - Jayaram, K; C.Arun, Dr (International Journal of Engineering and Technology, 2018)
Wireless communication system is a key element in modern uninterupted data tramsnission and reception services. In this paper, multi user Orthogonal Frequency Division Multiplexing (OFDM) system is designed with low power encoder and adaptive modualtion architectures. The proposed multi user encoder architecture is designed in Verlog HDL and simulated in Modelsim simulator. Xilinx Project Navigator is used to evaluate the performance of the proposed architecture interms of power consumptions and hardware utilizations by implementing the architecture on different virtex processors.